Changing Narratives of Intimate Partner Violence: A Longitudinal Photo-Ethnography. Issue 1 (1st June 2021) - Copes, Heith; Leban, Lindsay; Ragland, Jared
Abstract: We explore how women's narratives of abuse change, including narratives of self as well as narratives of their abusers. We draw on experiences from a photo-ethnography of people living in rural Alabama who use methamphetamine. The use of photographs taken throughout the project aid in both the representation of the women as well as in data collection (through photo-elicitation interviews). While we draw on the overall experiences from the project, we focus specifically on one key participant—Misty—to illustrate the ways that she made sense of and excused intimate partner violence, and how her narrative eventually changes. Our findings illuminate how the narratives people construct of themselves are intertwined with those they construct with others, and how such narratives change together.